Relationship quality among young couples from an economic and gender perspective - Britt, Sonya L.; Nazarinia Roy, R. Roudi (My University, 2013)
Less than a third of married couple households in the United States are composed of families with one breadwinner. This is a stark contrast to a mere 40 years ago when men were the primary breadwinner for the majority of households. The goal of this study was to determine how the perception of household chores is related to relationship quality. Specifically we wanted to determine how perception of household chores is related to relationship quality reported by partners from a traditional economic and a gender role theory perspective. Using data from the National Longitudinal Survey of Youth, 1986 cohort, results indicate that perceived unfair in household division of chores was predictive of women’s relationship quality, but not men’s. Arguments about affection and money were predictive of relationship quality for both genders.
Keywords: Married couple households; Household chores; Relationship quality; Gender role theory; Division of chores